Phitotherapeutic Potential of Cassava (Manihot esculenta, Crantz) - Cereda, Marney Pascoli [UNESP] (Springer Nature, 2023)
Cassava is a crop adapted to growing at 20° above and below the equator. Its roots are widely used as subsistence food and are of cultural importance, but its phytotherapic potential is little recognized or valued. This chapter highlights the cyanogenic, phenolic, and fiber compounds distributed throughout the cassava plant. The three components can have positive or negative health effects, with reports of good control of cancer cells. Although few reports have been made on their phototherapeutic effects, consumers of processed cassava products may enjoy them without being aware of their benefits because the presence of the three components in cassava-based foods is very common. This chapter presents data from the literature to justify the claims made about the crop.